WAYS OF THE TEACHER’S CREATIVE POTENTIAL DEVELOPMENT AND REALIZATION IN THE PROCESS OF PEDAGOGICAL ACTIVITIES - Обміняна, Галина; Яценко, Тамара (Modern engineering and innovative technologies, 2022)
The types of activity of the future teacher are surveyed in the article. The concept of the future teacher’s creative activity is defined, which is demonstrated in the state of readiness, striving for independent, original activities and choosing the best